2021
DOI: 10.1108/rjta-01-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Consumer expectations and perception of clothing comfort in sports and exercise garments

Abstract: Purpose Sports garments play an important role in the well-being of an athlete by protecting the wearer from changing environmental conditions and providing a comfortable feel. Clothing requirements have changed in recent years and demand for apparel with a higher comfort performance has been rising. Hence, the purpose of this study is to explore consumers’ expectations and perception of comfort and to examine how different textiles are perceived by consumers to provide useful knowledge that allows to engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Purchases made online often do not provide an adequate level of product information in comparison with purchases made in physical stores (Peck & Wiggins, 2006). Participants in an online survey asking about expectations, perceptions and preferences of clothing comfort, specifically of sportswear have expressed a need for touch (Wilfling, Havenith, Raccuglia, & Hodder, 2021). Need for touch refers to the person's desire to interact physically with the product.…”
Section: Visual-tactile Interplaymentioning
confidence: 99%
See 1 more Smart Citation
“…Purchases made online often do not provide an adequate level of product information in comparison with purchases made in physical stores (Peck & Wiggins, 2006). Participants in an online survey asking about expectations, perceptions and preferences of clothing comfort, specifically of sportswear have expressed a need for touch (Wilfling, Havenith, Raccuglia, & Hodder, 2021). Need for touch refers to the person's desire to interact physically with the product.…”
Section: Visual-tactile Interplaymentioning
confidence: 99%
“…For the interaction of the skin with textiles, however, tactile perception differences based on sex are widely unexplored. Studies investigating sex differences in online shopping found that women are more motivated by emotional and social interaction and that they enjoy a physical evaluation of products such as seeing and feeling the product before a purchase (Cho, 2004;Dittmar, Long, & Meek, 2004;Wilfling et al, 2021). Sex is a crucial factor affecting online as well as offline purchases since most apparel pieces are specifically designed for male or female customers.…”
Section: Evaluation Of Sex Differences In the Perception Of Textilesmentioning
confidence: 99%
“…Within the purchase process of sports textiles, the feel of garments has been identified as a crucial parameter, especially for female consumers [1]. Also, Li et al [2] found that the appreciation of textile products depends on a satisfactory 'feel' in the area of fabric -skin contact.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, sports t-shirts made from cotton and polyester were used in a wear trial, and the skin temperature, heart rate, body sweat loss and sweat absorption of garments were investigated. It was found that wearers preferred smooth, lightweight, and breathable fabrics under neutral environmental conditions 16 .The objective of the current study was to expose the t-shirt samples to a submaximal exercise test conducted by athletes with a specific rate of oxygen consumption value. This allowed for the assessment of various fibers' effects on athletes' performace.…”
mentioning
confidence: 99%
“…In another study, sports t-shirts made from cotton and polyester were used in a wear trial, and the skin temperature, heart rate, body sweat loss and sweat absorption of garments were investigated. It was found that wearers preferred smooth, lightweight, and breathable fabrics under neutral environmental conditions 16 .…”
mentioning
confidence: 99%